Estimation of post-mortem interval from vitreous potassium: An autopsy based study - Paul, Prince M; Sneha, S; Pradhan , Priyadarshee; Sampath Kumar, P (Journal of Indian Academy of Forensic Medicine, 2021)
Time since death which is the interval between death and the time of post-mortem examination is important during investigation of a crime. It is also called as ’post-mortem interval’ (PMI). A repeated problem in Forensic Medicine is the inability to fix the time when death occurred within the limits of probability. It is self-evident that more the duration between death and the examination of the body, longer will be the limits of probability. In this study, time since death was determined from potassium level in the vitreous humor and a formula was derived for the Chennai region. A prospective interventional study was conducted taking 75 vitreous samples. Potassium estimation was done using a fully automated analyzer- Siemens ADVIA1800. During the studied post-mortem period, a consistent liner rise of vitreous potassium was seen. The mean range of vitreous potassium concentration in the subjects varied between 5.4 mmol/L to 36.00 mmol/L (Mean ± SD, 19.30 ± 6.64). In the present study the average rate of increase of vitreous potassium was calculated as 0.931 mmol/L per hours with 95% confidence limit over ± 20 hours. The potassium-based formula derived from the present study to estimate PMI is: PMI = 1.075 (K+ mmol/L) – 2.53. The coefficient of correlation between post mortem interval and potassium concentration was found to be 0.997 in the present study, in comparison with studies done by Sturner & Gantner(1963). Vitreous potassium level linearly increase with time since death and can be used as a reliable parameter.